2000
DOI: 10.1161/01.res.87.8.710
|View full text |Cite
|
Sign up to set email alerts
|

Focal Adhesion Kinase Is Involved in Angiotensin II–Mediated Protein Synthesis in Cultured Vascular Smooth Muscle Cells

Abstract: The rate of vascular smooth muscle cell protein synthesis and cellular hypertrophy in response to angiotensin II (Ang II) is dependent on activation of protein tyrosine kinases (PTKs) and both the extracellular signal-regulated kinase (ERK) 1/2 and p70(S6K) pathways. One potential PTK that may regulate these signaling cascades is focal adhesion kinase (FAK), a nonreceptor PTK associated with focal adhesions. We used an actin depolymerizing agent, cytochalasin D (Cyt-D), and a replication-defective adenovirus e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 27 publications
5
49
0
Order By: Relevance
“…Only overexpression of a kinase-dead FAK (Gan et al, 2006) in 293 T cells or a dominant-negative FAK (FRNK) (Malik and Parsons, 1996) in chick embryo cells reduced phosphorylation of S6K1. Whether FAK really regulates S6K1 is challenged by other findings (Govindarajan et al, 2000) as well, because overexpression of FRNK did not affect phosphorylation of S6K1 in rat aortic vascular smooth muscle cells. The findings from this study and others (Jacinto et al, 2004) indicate that mTOR may regulate phosphorylation of the focal adhesion proteins, including FAK, paxillin and p130 Cas .…”
Section: Rapamycin Inhibition Of F-actin Reorganizationmentioning
confidence: 94%
“…Only overexpression of a kinase-dead FAK (Gan et al, 2006) in 293 T cells or a dominant-negative FAK (FRNK) (Malik and Parsons, 1996) in chick embryo cells reduced phosphorylation of S6K1. Whether FAK really regulates S6K1 is challenged by other findings (Govindarajan et al, 2000) as well, because overexpression of FRNK did not affect phosphorylation of S6K1 in rat aortic vascular smooth muscle cells. The findings from this study and others (Jacinto et al, 2004) indicate that mTOR may regulate phosphorylation of the focal adhesion proteins, including FAK, paxillin and p130 Cas .…”
Section: Rapamycin Inhibition Of F-actin Reorganizationmentioning
confidence: 94%
“…In cultured VSMC, it has been reported that angiotensin II increases phosphorylation of FAK and PYK2 (Govindarajan et al 2000;Rocic et al 2002); however, the differential effects of blood pressure and humoral factors remain to be elucidated. In the present study, we thus used the rat model of abdominal aorta-banding with the plasma levels of circulating humoral factors but with different blood pressure between the upper and lower bodies and the results indicated that circulating humoral factors may not substantially be involved in the phosphorylation of FAK and PYK2 in the present model.…”
Section: Humoral Factors and Vascular Remodelingmentioning
confidence: 99%
“…Phosphorylation of these kinases is accelerated by mechanical stress (Rice et al 2002;Iwasaki et al 2003). However, FAK and PYK2 could also be activated by angiotensin II, contributing to vascular remodeling in hypertension (Govindarajan et al 2000;Rocic et al 2002).…”
mentioning
confidence: 99%
“…6). FRNK can act as a dominant negative inhibitor of FAK signaling by localizing to focal adhesions, displacing FAK, and disrupting FAK signaling [149][150][151].…”
Section: Inhibiting Smc Proliferation and Migrationmentioning
confidence: 99%